PENGGUNAAN BATU KAPUR SUPER LOLOS #325 SEBAGAI FILLER PENGGANTI PADA CAMPURAN SPLIT MASTIC ASPHALT GRADING 0/11 - MAKMUN R. RAZALI (Universitas Bengkulu, 2019)
Split Mastic Asphalt ( SMA) was asphalt hotmix, first time developed and applied in Germany. In depelopment and experience, SMA suited for new highway, rehabilitation road and maintenance of road. The researched to know usage of super limestone pass siefe # 325 as substitution filler at mixture of SMA grading 0 / 11 to Marshall Property Result of research from all up to standard mixture was density, stability, flow and Marshall Question, except VITM and VMA